Industrial estates in Europe and the Middle East (United Nations, 1968)
Contents: Part I: Report of the United Nations Consultative Group on Industrial Estates and Industrial Areas in Cer-tain European and Other Countries in the Process of industrialization, Geneva, 24- 29 October 1966. Part II: Report of the United Nations Consultative Group on Industrial Estates and Industrial Areas in Arab Countries of the Middle East, Beirut, 31 October - 5 November 1966 ... .